A Simultaneous Approach to Improve Progress Payments System Using a Common Data Environment - Reneiloe Malomane; Innocent Musonda (Advances in Civil Engineering)
The success of a construction project depends on the efficiency in the processing, management, and payment of contractor progress claims regarding the activities that have been executed. The payments are made at intervals during the construction works of a project. These payments made to the contractor upon completion of a section of work, usually on a monthly basis, are known as progress payments. However, these progress payments are poorly managed, resulting in the contractor receiving monies late and, therefore, affecting the contractor’s cash flow. This poor management of payments is caused mainly by inadequate information management, poor communication, lack of collaboration, failure to agree on measurements of work done, and corruption. Thus, this study proposes a framework based on the common data environment (CDE) to effectively process and manage contractors’ progress payments. The study adopted a bibliometric and systematic literature review to identify current trends, scope, screen, select, and qualify prior knowledge on the subject. The findings reveal that implementing an effective CDE framework can promote efficient information management, communication, collaboration, and transparency. However, an effective CDE framework is dependent on training, policies, having a quality assurance team, and the adoption of appropriate digital tools to ensure the contractors’ progress payments are professionally managed. This study adds to the body of knowledge on the development of the CDE framework to manage progress payments and improve project success. The paper suggests that the implementation of a CDE is critical, but it is only effective if the suggested framework is applied.